Effect of deltamethrin insecticide sprayed frequencies towards Capsicum frutescens / Saiyidah Nafisah Hashim ... [et al.] - Hashim, Saiyidah Nafisah; Mohamed, Siti Mazleena; Abdullah, Siti Nur Azmu’i; Rodzali, Nur Nadirah; Wan Anuar, Wan Nurul Hidayah; Mohd Noor, Adibah; Mohd Khotob, Mohd Farid (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Deltamethrin is a synthetic pyrethroid insecticide with an extremely high activity level against many insects. It acts by both direct contact and ingestion. However, the application of this insecticide needs to be tested to understand the effect of its sprayed frequency on plant growth. The study aimed to investigate the effect of deltamethrin insecticide exposure on Capsicum frutescens. This experiment used an insecticide with a 2.8% active ingredient of deltamethrin diluted to 0.07% (v/v) according to product recommendation doses and sprayed on the C. frutescens plants at different frequencies for two weeks. The measured parameters are deltamethrin insecticide's effect on plant leaves (visual inspection, starch, and chlorophyll analysis) and soil (pH, water content and organic content). Results show that the deltamethrin insecticides successfully inhibited the invasion of aphids; however, the plant leaves gave positive signs of phytotoxicity. Other than that, the spray frequencies reduced the plants' starch, and chlorophyll content caused the green color to become less intense. The plant soil analysis found that the deltamethrin insecticide at both sprayed frequencies had caused an increase in the soil pH and reduced water and organic content. Overall, the application of deltamethrin at these studied frequencies has been found to detrimentally impact both the plants' growth and the soil's quality. Therefore, it is imperative to optimize the exposure of this insecticide by allowing minimal frequencies lower than those tested in this study.